Classification of Pandavas Figure in Shadow Puppet Images using Convolutional Neural Networks - Supriyanti, Wiwit; Anggoro, Dimas Aryo (Khazanah Informatika, 2021)
Indonesia is a nation with various ethnicities and rich cultural backgrounds that span from Sabang to Merauke. One of the cultural products of Indonesian society is shadow puppet. Shadow puppet has been internationally renowned as a masterpiece of cultural art and recognized by UNESCO. The development of Indonesian society is very dependent on technological sophistication and it may shift the existing traditional culture out from the memory of the nation. Practices of modern life and the busy activities of the people exacerbate the condition and may make the society to ignore traditional culture. This study seeks to preserve traditional Indonesian culture by making shadow puppets as the object of classification. We use a deep learning algorithm called convolutional neural network (CNN) to classify 430 puppet images into 4 classes. The proportion of training, validation and test data is 70 by 20 by 10. The experiments show that the most efficient model is obtained with 3 convolution layer. It reaches an accuracy rate of 0.93 and a drop out rate of 0.2